2002
DOI: 10.1073/pnas.242251499
|View full text |Cite
|
Sign up to set email alerts
|

Neurovestibular modulation of circadian and homeostatic regulation: Vestibulohypothalamic connection?

Abstract: Chronic exposure to increased force environments (+G) has pronounced effects on the circadian and homeostatic regulation of body temperature (T(b)), ambulatory activity (Act), heart rate, feeding, and adiposity. By using the Brn 3.1 knockout mouse, which lacks vestibular hair cells, we recently described a major role of the vestibular system in mediating some of these adaptive responses. The present study used the C57BL6JEi-het mouse strain (het), which lacks macular otoconia, to elucidate the contribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
89
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 29 publications
(13 reference statements)
8
89
0
1
Order By: Relevance
“…In these situations, sleep and circadian disruptions could have serious consequences on the effectiveness, health, and safety of astronaut crews (46,47). Moreover, long-duration exploration class space missions may require astronauts to be scheduled to non-24-h light:dark periods for extended durations of time in conditions in which gravity could additionally impact circadian physiology (48). The above issues highlight the importance of developing effective countermeasures to maintain circadian entrainment.…”
Section: Discussionmentioning
confidence: 99%
“…In these situations, sleep and circadian disruptions could have serious consequences on the effectiveness, health, and safety of astronaut crews (46,47). Moreover, long-duration exploration class space missions may require astronauts to be scheduled to non-24-h light:dark periods for extended durations of time in conditions in which gravity could additionally impact circadian physiology (48). The above issues highlight the importance of developing effective countermeasures to maintain circadian entrainment.…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected by our performance on the single most safety-sensitive task that is shared in common by most American adults: driving motor vehicles on the nation's highways. This routine highly over-learned task performed in a moving vehicle, the motion of which stimulates the neurovestibular input to the ventrolateral preoptic (VLPO) area (Fuller et al 2002), provides a setting that can unmask elevated homeostatic sleep drive. Sleep loss and misalignment of circadian phase increase the likelihood that the VLPO area of the hypothalamus will initiate an involuntary transition from wakefulness to sleep (Saper et al 2005).…”
Section: Drowsy Drivingmentioning
confidence: 99%
“…The vestibular system is primarily involved in gaze stabilization and postural control (23), but its influence has been expanded to autonomic and bone regulation (11,61,63), spatial learning and memory (5, 6, 56), and spatial orientation and perception of gravitational verticality (37). Studies carried out in environments in which gravity is altered have shown evidence of a possible influence of the vestibular system on hypothalamic circadian function in rats (27) and mice (18,46 …”
mentioning
confidence: 99%
“…The vestibular system is primarily involved in gaze stabilization and postural control (23), but its influence has been expanded to autonomic and bone regulation (11,61,63), spatial learning and memory (5,6,56), and spatial orientation and perception of gravitational verticality (37). Studies carried out in environments in which gravity is altered have shown evidence of a possible influence of the vestibular system on hypothalamic circadian function in rats (27) and mice (18,46); disruption of circadian rhythms of temperature (Temp) and locomotor activity (Act) have been similarly observed in both species for about 7 days in a 2 G environment generated by a centrifuge. Knockout mice devoid of otolithic vestibular sensors [het(Ϫ/Ϫ) mice] remained unaffected by hypergravity at 2 G (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation